2015
DOI: 10.1111/mmi.13040
|View full text |Cite
|
Sign up to set email alerts
|

ComGARelA interaction and persistence in the Bacillus subtilisK‐state

Abstract: Summary The bistably expressed K-state of Bacillus subtilis is characterized by two distinct features; transformability and arrested growth when K-state cells are exposed to fresh medium. The arrest is manifested by a failure to assemble replisomes and by decreased rates of cell growth and rRNA synthesis. These phenotypes are all partially explained by the presence of the AAA+ protein ComGA, which is also required for the binding of transforming DNA to the cell surface and for the assembly of the transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 86 publications
(132 reference statements)
0
48
0
Order By: Relevance
“…The K-state appears to be a persistent state in which a trade off between the costs of growth-arrest and the expression of the competence machinery are balanced by fitness benefits due to tolerance in the face of environmental insults, e.g., exposure to antibiotics (Nester and Stocker, 1963; Johnsen et al, 2009; Hahn et al, 2015; Yuksel et al, 2016), as well as the ability to acquire useful genetic information. In the face of this trade-off, bet-hedging due to the bistable expression of the K-state, presumably helps to maximize fitness (Dubnau and Losick, 2006; Veening et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The K-state appears to be a persistent state in which a trade off between the costs of growth-arrest and the expression of the competence machinery are balanced by fitness benefits due to tolerance in the face of environmental insults, e.g., exposure to antibiotics (Nester and Stocker, 1963; Johnsen et al, 2009; Hahn et al, 2015; Yuksel et al, 2016), as well as the ability to acquire useful genetic information. In the face of this trade-off, bet-hedging due to the bistable expression of the K-state, presumably helps to maximize fitness (Dubnau and Losick, 2006; Veening et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Because these genes are not needed for transformation (J. Hahn, unpublished) the expression of ComK must result in phenotypes beyond competence that presumably enhance fitness. In fact, ComK also induces a period of growth arrest during which the cells that express ComK exhibit antibiotic tolerance (Nester and Stocker, 1963; Haijema et al, 2001; Johnsen et al, 2009; Briley et al, 2011; Hahn et al, 2015; Yuksel et al, 2016). This persistent state has been called the K-state, to emphasize that ComK regulates more than competence for transformation (Berka et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among the proteins encoded by these genes are those that enable the uptake and processing of transforming DNA; K-state cells are thus genetically competent for transformation. In addition, K-state cells are arrested for growth and division and are tolerant of a number of antibiotics (Hahn et al, 2015). Importantly, the K-state is bistably expressed, turning on in a subpopulation of cells.…”
Section: Introductionmentioning
confidence: 99%
“…New microscopy approaches are emerging to better comprehend the mechanisms involved in the process of transformation. In recent times, several studies revealed the formation of tDNA foci on the surface of competent bacteria (Stingl et al, 2010;Berge et al, 2013;Gangel et al, 2014;Hahn et al, 2015;Kruger et al, 2016). Only one group followed by microscopy the tDNA passage into the cytoplasm .…”
Section: Introductionmentioning
confidence: 99%